2019
DOI: 10.1021/acscatal.9b00231
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic Carbon–Hydrogen and Carbon–Fluorine Bond Cleavage through Hydroxylation Promoted by a Histidyl-Ligated Heme Enzyme

Abstract: LmbB2 is a peroxygenase-like enzyme that hydroxylates L-tyrosine to L-3,4-dihydroxyphenylalanine (DOPA) in the presence of hydrogen peroxide. However, its heme cofactor is ligated by a proximal histidine, not cysteine. We show that LmbB2 can oxidize L-tyrosine analogs with ring-deactivated substituents such as 3-nitro-, fluoro-, chloro-, iodo-L-tyrosine. We also found that the 4-hydroxyl group of the substrate is essential for reacting with the heme-based oxidant and activating the aromatic C-H bond. The most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(63 citation statements)
references
References 64 publications
4
59
0
Order By: Relevance
“…, the b -type heme-containing tyrosine hydroxylase, LmbB2. 10 Collectively, these results indicated that the loss of the single cysteine–vinyl covalent linkage through mutation led to heme with an electronic structure reminiscent of b -type heme and results in a catalytically inactive variant.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…, the b -type heme-containing tyrosine hydroxylase, LmbB2. 10 Collectively, these results indicated that the loss of the single cysteine–vinyl covalent linkage through mutation led to heme with an electronic structure reminiscent of b -type heme and results in a catalytically inactive variant.…”
Section: Resultsmentioning
confidence: 95%
“…7 SfmD requires a mononuclear heme as its prosthetic group for oxygenation, similar to enzymes with analogous activity, i.e., heme-based tyrosine hydroxylases (TyrH), 8 including LmbB2 and Orf13. [9][10][11] Such a cofactor dependency for aromatic amino acid oxidation is mechanistically distinct from other types of tyrosine hydroxylation mediated by nonheme-dependent monooxygenases such as pterin-dependent tyrosine hydroxylase, 12,13 copper-dependent tyrosinase, 14 and the two-component, FADdependent monooxygenase found in SgcC. 15 SfmD was previously reported as a heme peroxidase with an atypical peroxidase activity of hydroxylating 3-Me-L-Tyr or L-Tyr using hydrogen peroxide as oxidant.…”
Section: Introductionmentioning
confidence: 98%
“…At the same time 3-fluoro-5-hydroxyl-l-tyrosine is also produced by oxidative C-H bond cleavage at C5 in the same reaction mediated by LmbB2 (Fig. 8) [37].…”
Section: Enzymes Involved In Defluorination Of Fluorinated Aromaticsmentioning
confidence: 88%
“…Peroxygenase-like LmbB2 (histidyl-ligated heme enzyme) coded by the lmbB2 gene of the lincomycin biosynthesis gene cluster in Streptomyces lincolnensis catalyzes the defluorination of 3-fluorotyrosine to yield 3,4-dihydroxyphenylalanine (DOPA) under the presence of H 2 O 2 (Fig. 8) [37]. At the same time 3-fluoro-5-hydroxyl-l-tyrosine is also produced by oxidative C-H bond cleavage at C5 in the same reaction mediated by LmbB2 (Fig.…”
Section: Enzymes Involved In Defluorination Of Fluorinated Aromaticsmentioning
confidence: 99%
“…Although the C-F bond is the strongest covalent single bond in organic chemistry, cysteine dioxygenase is able to cleave a C-F bond to realize co-factor biogenesis (see Scheme 5a). In 2019, Wang's group discovered that a histidine-linked heme enzyme can catalyze the cleavage of C-F by hydroxylation (Wang et al 2019). LmbB2 has a wide range of catalytic activities toward l-tyrosine analogues, as long as the 4-hydroxyl group is present.…”
Section: Enzyme-catalyzed C-f Bond Cleavagementioning
confidence: 99%